Adipogenesis in Different Body Depots and Tumor Development - Trivanović, Drenka; Vignjević Petrinović, Sanja; Okić Djordjević, Ivana; Kukolj, Tamara; Bugarski, Diana; Jauković, Aleksandra (Frontiers in Cell and Developmental Biology, 2020)
Anatomically localized at different body sites, adipose tissue (AT) form depots in subcutaneous and visceral regions, as well as bone marrow. These ATs differ in organization of adipocyte functional profile, insulin sensitivity, adipokines’ production, lipolysis and their homeostasis and response to pathologic conditions. Although recent advances in lineage tracing demonstrated individual adipose depots composed of adipocytes derived from distinct progenitor populations, cellular and molecular dissection of adipose clonogenic stem cell niche is still great challenge. AT microenvironment and different phenotype outcomes of differentiating adipogenic lineages are found to be an integrative and enforcing unit of cell differentiation and regulation of healthy and neoplastic phenotype manifestation. Tumor development is followed by AT capacity to impose and support aberrant potency on stem cells. In this review we summarize current findings on communication of adipocytes and their progenitors with tumor cells, pointing out to the co-existence of healthy (adipogenic) and neoplastic stem cell niche as well, developed during tumor evolution. Tumor-induced adaptations in mature adipocytes and involvement of an alternative differentiation programs are discussed.